Goals and prospects of carpet industry development in Uzbekistan - Musayeva Shoira Azimovna; Usmonova Dilfuza Ilkhomovna (Genius Journals, 2021)
The article examines the activities of carpet manufacturing enterprises, the most promising segment of the textile industry in Uzbekistan, analyzes the competitive environment of participants in the local carpet market, and analyzes the principles of a scientific approach to marketing
Keywords: Enterprise; industry; market; carpet